(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
People in the state still think of the library system as little more than a repository for booksand recorded information. It is common practise to refer to the librarian as a keeper or custodian of thebooks. The primary service that patrons require in this day and age, the notion of libraries has evolved tothe point that they are now open all day, every day of the week. The services that libraries provide havebeen modified. They have reached a very advanced level in the field of research and development, andup-to-date material is made available to scholars and researchers. The role of libraries is evolvingtowards that of service institutions.More than a quarter of library users are highly happy with thelibrary’s amenities, including the library area, library access system, reading hall seating capacity, andsecurity system.Library users should be made aware of the many study resources. It’s important toimprove the library’s amenities to attract more customers.